Efficient humidity sensor based on surfactant free Cu2ZnSnS4 nanoparticles. Issue 19 (1st October 2022) - Patil, Urmila; Dhanasekar, M.; Kadrekar, Riddhi; Arya, A.; Bhat, S. Venkataprasad; Late, Dattatray J.
Abstract: In addition to their proved potential in thin film photovoltaics, the nanoparticles of Cu2 ZnSnS4 (CZTS) are also identified as one of the promising candidates for developing next generation humidity sensors. However, the surfactants generally used during their synthesis often lead to more organic residue and adversely affect the sensing behaviour. Herein, we report on the CZTS nanoparticles synthesized using two surfactant free routes and their improved humidity sensing behaviour. CZTS1 and CZTS2 nanoparticles made using the hydrothermal and molecular precursor aging method exhibited very high response of ∼3218.44 and ∼32115.07 respectively, as observed with 97%RH at room temperature. The exceptional response shown by the CZTS nanoparticles could be attributed to the relatively smaller crystalline sizes and larger number of good quality adsorption sites, as understood with the help of the density functional theory calculations. The calculations also indicate that, the slower response and recovery could be explained based on the stronger adsorption of water molecules on the CZTS surface. The results confirm the potential of the quaternary sulphide compound to be used in efficient humidity sensors and establish the role of the surfactant free synthesis method for achieving a significant improvement in the sensing ability. Graphical abstract: Image 1